Sistem Informasi Penerimaan Dan Pengeluaran Barang Berbasis WEB - Elsa Aulia Lubis (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Nowadays, technology has experienced very rapid progress, contributing to all fields, especially for companies. Company activities are basically aimed at obtaining profits or very satisfying results, to achieve these goals the company must know how to do it. One of the resources that has a great influence on activities is humans (workforce) where the workforce (humans) is the main factor in the success of the company in achieving its goals. PT. Perkebunan Lembah Bhakti requires an integrated system (People, Process, Technology) to solve problems, namely: availability of incoming and outgoing goods, the current system is more complex and inefficient, and many manual processes to create consolidation and reports. The hope for a new integration system is a more optimal business process (synergy and integration), to improve data accuracy, information speed, data and information security and system reliability, increase analytical power so that decisions can be made accurately and quickly. With the design of this goods receipt and expenditure system, it is hoped that it can facilitate data input, receipt of goods, expenditure of goods and can provide information whenever needed.